f? - statistical convergence in topological groups - Sarikaya, Suleyman; Altin, Yavuz (Univ Nis, Fac Sci Math, 2024)
In this paper, the concept of f(lambda) - statistical convergence is generalized to topological groups with the help of unbounded modulus function. Furthermore, the relationship between the notions of f - statistically convergent and f(lambda) - statistically convergent is investigated and some related inclusion results are proved in topological groups using properties of the modulus function. Additionally, this relationship was given in different modulus functions.
Keywords: topological groups; sequence spaces; statistical convergence; modulus function.